The Practical Barriers to Auction of Confiscated Objects for Corruption Crime - Gholibuddin Zuhairmanto; Retno Saraswati; Kornelius Benuf (Jurnal Daulat Hukum, 2022)
This study aims to determine the implementation of the auction of confiscated objects of corruption carried out by the Kulon Progo District Attorney, as well as to find out the obstacles that exist in the process of auctioning confiscated objects of corruption. This study uses a research method with an empirical juridical approach, and a descriptive analytical research specification. This research was conducted at the Kulon Progo District Attorney's Office. The crime of corruption in recent decades has become an issue that has been widely discussed in both print and electronic media by all members of the public, because several persons suspected of committing a criminal act of corruption cannot be separated from office holders in Indonesia, consisting of executives, Legislative and even up to the Judiciary. Based on the research results, it is known that the auction implementation based on PMK No. 27/PMK.06/2016 concerning Instructions for Implementation of Auctions and PMK No. 13/PMK.06/2018 Concerning the Auction of Confiscated Objects, State Loot, or Executed Confiscated Objects Originating from the Prosecutor's Office of the Republic of Indonesia. The obstacles encountered by the Kulon Progo District Attorney's Office in the auction process, such as in the case of correspondence between the Prosecutor's Office and the KPKNL, the length of time the results of the trial came out which could result in a decrease in the value of the confiscated goods. Problems related to the implementation of electronic auctions are also still an obstacle.